Verticillium dahliae manipulates plant immunity by glycoside hydrolase 12 proteins in conjunction with carbohydrate‐binding module 1. (28th March 2017) - Gui, Yue‐Jing; Chen, Jie‐Yin; Zhang, Dan‐Dan; Li, Nan‐Yang; Li, Ting‐Gang; Zhang, Wen‐Qi; Wang, Xin‐Yan; Short, Dylan P. G.; Li, Lei; Guo, Wei; Kong, Zhi‐Qiang; Bao, Yu‐Ming; et al.
Summary: Glycoside hydrolase 12 (GH12) proteins act as virulence factors and pathogen‐associated molecular patterns (PAMPs) in oomycetes. However, the pathogenic mechanisms of fungal GH12 proteins have not been characterized. In this study, we demonstrated that two of the six GH12 proteins produced by the fungus Verticillium dahliae Vd991, VdEG1 and VdEG3 acted as PAMPs to trigger cell death and PAMP‐triggered immunity (PTI) independent of their enzymatic activity in Nicotiana benthamiana . A 63‐amino‐acid peptide of VdEG3 was sufficient for cell death‐inducing activity, but this was not the case for the corresponding peptide of VdEG1. Further study indicated that VdEG1 and VdEG3 trigger PTI in different ways: BAK1 is required for VdEG1‐ and VdEG3‐triggered immunity, while SOBIR1 is specifically required for VdEG1‐triggered immunity in N. benthamiana . Unlike oomycetes, which employ RXLR effectors to suppress host immunity, a carbohydrate‐binding module family 1 (CBM1) protein domain suppressed GH12 protein‐induced cell death. Furthermore, during infection of N. benthamiana and cotton, VdEG1 and VdEG3 acted as PAMPs and virulence factors, respectively indicative of host‐dependent molecular functions. These results suggest that VdEG1 and VdEG3 associate differently with BAK1 and SOBIR1 receptor‐like kinases to trigger immunity in N. benthamiana, and together with CBM1‐containing proteins manipulate plant immunity.